HISTORICAL ASPECTS OF THE ACTIVITIES AND ORGANIZATIONS BY DON PHARMACY - T. G. DERGOUSOVA (Кубанский научный медицинский вестник, 2017)
This article examines the historical aspects of the creation of pharmacy organizations in the Don from the beginning of the 18th century. The development of the pharmaceutical business of our region is associated with the names of the great men of the time: in the villages of the Don Cossacks – the Empress Elizabeth, troop Ataman Platov; Taganrog – Catherine the Great and Alexander I; Rostov-on-Don – the Emperor Nicholas II. Social and economical environments of that time, geographical position and climate had an influence on it . It was found that during the 200 years of pharmacy service on the Don, pharmacy workers, along with trading activities, engaged in charity, prevention and first aid.